التّحفيز في رواية "سجين المرايا" للكاتب سعود السّنعوسي: بنيته ودلالاته - بوزكور, مراد (جامعة الوادي - university of Eloued, 2022)
ملخص: يهدف هذا المقال إلى تقديم مقاربة شكلانية لبنية التّحفيز (Motivation) في رواية "سجين المرايا" للكاتب سعود السنعوسي. وقد شغل هذا المصطلح - باعتباره آليّة قرائية للنّصوص السّردية- اهتمام الشّكلانيين الرّوس والبنيويين، نظرا لما تحقّقه هذه الآلية من نتائج علمية في وصف اشتغال النظام السّردي. وسيركّز هذا المقال على وصف اشتغال نسقين أساسين من أنساق التّحفيز، وهما: التّحفيز السّياقي وتحفيز الدّلالة الموضوعية . Abstract: This article aims to present a formal approach to the novel "The Prisoner of Mirrors" of Saud Al-Sanousi, using the Motivation mechanism as a method of reading. This term - as a reading mechanism for the narrative texts - occupied the interest of the Russian Formalists and the Structuralists due to the scientific results that this mechanism achieves in describing the operation of the narrative system. This article will focus on describing the operation of two modes of Motivation, namely: contextual Motivation and objective semantic Motivation.
Motivation In The Novel "prisoner Of Mirrors" By The Writer Saud Al-sanousi : Its Structure And Its Connotations
مقال
Keywords: الشكلانيّة ؛النّسق السّردي؛ التّحفيز ؛التّحفيز السّياقي؛ تحفيز الدّلالة الموضوعية; Formalism; Narrative mode; Motivation ;Contextual motivation; Objective semantic motivation.